The experiences of nurses regarding attendance, engagement and accessibility of continuous professional development at a tertiary hospital, eastern region, Saudi Arabia - Doughty, Valerie Dolores (Stellenbosch : Stellenbosch University, 2021)
Thesis (MNur)--Stellenbosch University, 2021.